Mathematical Modelling of Flood Propagation for the Delimitation of Rural, Semiurbanized and Urbanized zones with Inundation Risk - Riccardi, Gerardo A. (1997)
A mathematical model of subcritical flow simulation is described in this paper. It's capable for flood propagation in water courses with flood plains partial or totally obstructed. Also it permits the simulation in semiurbanized and urbanized zones , modelling the flow through the ground surface (major system) and through conduit networks (minor system). The model was calibrated by simulation of several events with recorded information and now this is being applied as a technical tool in the risk zone delimitation of floods with different retum period in the Luduena Stream, water course of the Rosario District. In this work the goveming equations of the model are exposed. Later the numeric formulation, the solution of the equations in kite differences, the boundary and initial conditions, and the computational structure are presented. Then the state of advance of a model application is described. This application consists in the model ling on: 15 km of water course, 1.5 km on big underground conduits, embracing a zone of 40 km2 in the rural and urban zone of the cities of Rosario and Funes. Lastly the conclusions of the work are exposed.